The Effect of Alendronate and Calcitonin Treatments on Bone Mineral Density and Quality of Life in Women With Postmenopausal Osteoporosis - F. Taşçıoğlu; C. Öner; O. Armağan; İ. Dalkıran; E. Sırmagül (Galenos Yayinevi, 2002)
The aim of this study was to compare the effect of alendronate and calcitonin treatments on bone mineral density (BMD) and quality of life of women with postmenopausal osteoporosis. One hundred ninety-three patients were randomly assigned to two groups: 93 patients received daily doses of 10 mg alendronate and calcium 1000 mg, and 98 patients used intranasal salmon calcitonin (sCt) at a dosage of 200 IU/day and they also received daily doses of 1000 mg calcium supplements. DXA was used for the measurement of BMD of the lumbar spine and proximal femur before and after the study period. SF-36 was used as a measure of health-related quality of life. At the end of the treatment, ALN produced significant increases in BMD at the lumbar spine (p< 0.001), femur neck (p<0.05), trochanteric region (p<0.001) and at the Ward triangle (p<0.05). In contrast, intranasal sCt treatment resulted in a significant bone loss in the femur neck (p<0.01) and Ward triangle (p<0.05), and only a significant increase in BMD of the lumbar spine was observed with calcitonin treatment(p< 0.05). Quality of life as assessed by SF-36 improved significantly in both groups(p<0.05). In conclusion, alendronate seemed to be more effective than calcitonin, increasing both spinal and femoral BMD, for the treatment of postmenopausal osteoporosis. Both treatments were found to be effective for the improvement of quality of life.